2017
DOI: 10.1021/acs.est.7b05217
|View full text |Cite
|
Sign up to set email alerts
|

Increases of Total Mercury and Methylmercury Releases from Municipal Sewage into Environment in China and Implications

Abstract: As a globally transported pollutant, mercury (Hg) released from human activity and methylmercury (MeHg) in the food web are global concerns due to their increasing presence in the environment. In this study, we found that Hg released from municipal sewage into the environment in China is a substantial anthropogenic source based on mass sampling throughout China. In total, 160 Mg (140-190 Mg, from the 20th percentile to the 80th percentile) of Hg (THg) and 280 kg (240-330 kg) of MeHg were released from municipa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
86
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 71 publications
(95 citation statements)
references
References 67 publications
(167 reference statements)
4
86
1
Order By: Relevance
“…The increase indicates that terrestrial ecosystems in China have received extensive inputs of anthropogenic THg (including direct and legacy sources) in the last several decades. 27,47 A previous study found that 530 Mg of anthropogenic THg was emitted into the atmosphere in 2014 in China and had increased rapidly from 250 Mg in 1990, consistent with our estimates on the increasing rate. 24 However, the THg release from direct industrial sources into surface soils still lacks adequate quantification in China.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…The increase indicates that terrestrial ecosystems in China have received extensive inputs of anthropogenic THg (including direct and legacy sources) in the last several decades. 27,47 A previous study found that 530 Mg of anthropogenic THg was emitted into the atmosphere in 2014 in China and had increased rapidly from 250 Mg in 1990, consistent with our estimates on the increasing rate. 24 However, the THg release from direct industrial sources into surface soils still lacks adequate quantification in China.…”
Section: Resultssupporting
confidence: 91%
“…The concentration in Tibet around 2010 was 2.6-fold higher than that around 1990 due to the increase in human activity in this area; for example, it has the highest per capita THg release from domestic sewage among all provinces in China. 27 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations